Enhanced performance of spin-coated silver-modified titanium dioxide thin films over dip coating method for metformin photodegradation - D’ April Sabriantie Mulus; Muhamad Diki Permana; Sarah Puteri Hayaa’ Prawiranegara; Calya Zahira Tustika; Syelena Prima Putri; Salwa Aulia Zahra; Yusi Deawati; Diana Rakhmawaty Eddy (Results in Optics)
Thin film photocatalyst arises as an alternative material for metformin degradation with great recovery and reusability. However, different sol–gel deposition methods namely spin coating and dip coating will affect the characteristics of thin film due to different deposition rates, which affect its surface morphology and its photocatalytic activity. This research aims to compare two different sol–gel deposition methods to synthesize Ag-modified TiO2 thin films to their characteristics, including surface morphology, crystal structure, optical properties, and photocatalysis efficiency towards metformin. In this research, Ag-TiO2 sol was coated on glass substrates by two different deposition methods namely manual dip coating (DC) and spin coating (SC) method, and annealed at 500℃. The amorphous-dominant phase is formed by the DC method, while the anatase crystalline phase is formed by the SC method. Ag-TiO2 thin film synthesized by the SC method gives a lower band gap than the DC method. The TM-EDS revealed that the SC method gives a more uniform morphology and high incorporation of Ag. The photocatalytic test shows an increase in activity with Ag modification approximately 4–5 times from pure TiO2 thin films with the highest degradation percentage of 22.05 % within 150 min using UVA irradiation achieved by the Ag-TiO2 thin film deposited by the SC method. This concludes that the spin coating method gives a greater characteristic of Ag-TiO2 thin film and enhances its photocatalytic activity.